2014
DOI: 10.3904/kjim.2014.29.4.454
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of infarct severity from triiodothyronine levels in patients with ST-elevation myocardial infarction

Abstract: Background/AimsThe aim of the present study was to evaluate the relationship between thyroid hormone levels and infarct severity in patients with ST-elevation myocardial infarction (STEMI).Methods We retrospectively reviewed thyroid hormone levels, infarct severity, and the extent of transmurality in 40 STEMI patients evaluated via contrast-enhanced cardiac magnetic resonance imaging.ResultsThe high triiodothyronine (T3) group (≥ 68.3 ng/dL) exhibited a significantly higher extent of transmural involvement (la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 42 publications
0
27
0
1
Order By: Relevance
“…Lymvaios et al also reported a strong association of low T3 with impaired ventricular function among AMI patients, concluding that T3 levels may represent a predictor of ventricular functional recovery . Interestingly, the findings of another study exhibited that the extent of transmural involvement in patients with STEMI, assessed by cardiac magnetic resonance imaging 40 days after the event, is strongly associated with T3 levels . In this retrospective and small‐sized study, the group with high/normal T3 levels had a significantly greater extent of transmural involvement than the low‐T3 group, which presented a significantly larger myocardial area at risk, thus a greater extent of ischemia and an increased myocardial salvage index .…”
Section: Prognostic Value Of Thyroid Hormones In Acsmentioning
confidence: 55%
See 3 more Smart Citations
“…Lymvaios et al also reported a strong association of low T3 with impaired ventricular function among AMI patients, concluding that T3 levels may represent a predictor of ventricular functional recovery . Interestingly, the findings of another study exhibited that the extent of transmural involvement in patients with STEMI, assessed by cardiac magnetic resonance imaging 40 days after the event, is strongly associated with T3 levels . In this retrospective and small‐sized study, the group with high/normal T3 levels had a significantly greater extent of transmural involvement than the low‐T3 group, which presented a significantly larger myocardial area at risk, thus a greater extent of ischemia and an increased myocardial salvage index .…”
Section: Prognostic Value Of Thyroid Hormones In Acsmentioning
confidence: 55%
“…Interestingly, the findings of another study exhibited that the extent of transmural involvement in patients with STEMI, assessed by cardiac magnetic resonance imaging 40 days after the event, is strongly associated with T3 levels . In this retrospective and small‐sized study, the group with high/normal T3 levels had a significantly greater extent of transmural involvement than the low‐T3 group, which presented a significantly larger myocardial area at risk, thus a greater extent of ischemia and an increased myocardial salvage index . The authors concluded that the transient low T3 state during AMI is associated with lower transmurality, suggesting a protective role of the low T3 syndrome.…”
Section: Prognostic Value Of Thyroid Hormones In Acsmentioning
confidence: 77%
See 2 more Smart Citations
“…A high T3 level was an independent predictor of transmural involvement after adjustment for the presence of Diabetes Mellitus and the use of glycoprotein IIb/IIIa inhibitors [74].…”
Section: Thyroid Hormones and Acute Cardiac Diseasesmentioning
confidence: 94%